2002
DOI: 10.4049/jimmunol.169.7.3555
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Impacts of Immunosuppressive Agents (Rapamycin, FK506, Cyclosporin A, and Dexamethasone) on Bidirectional Dendritic Cell-T Cell Interaction During Antigen Presentation

Abstract: Rapamycin (RAP), tacrolimus (FK506), cyclosporin A, and glucocorticoids represent modern and classic immunosuppressive agents being used clinically. Although these agents have distinct molecular mechanisms of action and exhibit different immunoregulatory profiles, their direct influences on Ag presentation processes remain relatively unknown. Here we report quantitative and qualitative differences among the above four immunosuppressants in their impact on Ag-specific, bidirectional interaction between dendriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
96
2
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 54 publications
(44 reference statements)
9
96
2
1
Order By: Relevance
“…As shown in Fig. 3A, 35 S-incorporated HIF-1␣ was clearly detected not in the cells without stimulation but in those treated with anti-CD3 mAb in the presence of MG132 (Fig. 3A), indicating that in addition to the inhibition of degradation, an up-regulation of HIF-1␣ protein synthesis by TCR ligation contributes to HIF-1␣ protein accumulation.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…As shown in Fig. 3A, 35 S-incorporated HIF-1␣ was clearly detected not in the cells without stimulation but in those treated with anti-CD3 mAb in the presence of MG132 (Fig. 3A), indicating that in addition to the inhibition of degradation, an up-regulation of HIF-1␣ protein synthesis by TCR ligation contributes to HIF-1␣ protein accumulation.…”
Section: Resultsmentioning
confidence: 86%
“…Moreover, we have shown that rapamycin represses mRNA expression of HIF-1 target genes including PGK1, and GLUTs, which serve as key molecules for glycolysis, as well as that of VEGF. It should be noted that mRNA expression of, for example, IL-2 was reported not to be susceptible to treatment with rapamycin (35). Since the promoter region of the IL-2 gene does not contain HRE, we may conclude that rapamycin rather selectively targets HRE-containing genes and elicits distinct immunosuppression via, at least in part, repression of HIF-1-dependent gene expression (35).…”
Section: Discussionmentioning
confidence: 99%
“…The point is whether this intratumoral IL-12 gene therapy is effective in other immunosuppressants, including cyclophosphamide, mycophenolate mofetil, steroids, and rapamycin, which have been favorably used to control rejection at present. Matsue et al (59) reported that FK506 or cyclosporin A, which were both calcineurin inhibitors, more effectively suppress the priming of the T cell, including IFN-␥ production, and dendritic cells in the T cell-dendritic cell direction in vitro than rapamycin and steroids. Lui et al (60) reported that cyclosporin A more effectively suppresses IFN-␥ production of T cells at the priming in vivo than mycophenolate mofetil.…”
Section: Discussionmentioning
confidence: 99%
“…Of Th2 cytokines, IL-4 and IL-10 showed synergistic Colchicine-derived compound CT20126 promotes skin allograft survival by regulating the balance of Th1 and Th2 cytokine production and antagonistic immunoregulatory capacities, such as elevation of Th2 cytokine gene expression and suppression of NO production and macrophage cytotoxic activity (Oswald et al, 1992;SchmidtWeber et al, 1999), leading to prolongation of allograft survival (Furukawa et al, 2005). In addition, treatment with immunosuppressants such as tacrolimus and sirolimus decreased capacity to produce Th1-mediated pro-inflammatory cytokines and prolonged allograft survival (Matsue et al, 2002). It indicates that the expression levels of Th1 and Th2 cytokines are thought to play an important role in the regulation of tolerance in organ transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…All these drugs affect not only the cells of the immune system, but have some adverse functions on other cells or tissues (Saeed et al, 2006). These immunosuppressants have been shown to inhibit the production of nitric oxide (NO), IL-1 , and TNF-as cytotoxic molecules participating in graft rejection by graft-infiltrating macrophages (Krulova et al, 2002;Matsue et al, 2002). The level of NO produced after transplantation correlates with the kinetics of rejection reaction and with the fate of the graft using an experimental mouse model (Krulova et al, 2002).…”
Section: Introductionmentioning
confidence: 99%